Feminism in the Short Story “Eveline” by James Joyce - Martina Girsang; Lio Naomi Situmorang; Dona Chrystina Situngkir; Imanuela Elpride; Yemima Vrianita Simangunsong (Departement of Mathematics Education, 2023)
The message is conveyed by the author (writer) which is conveyed either explicitly or implicitly “Eveline” is a short story written by James Joyce. This short story was published in 1904 with a story setting around the same year and decade. The short story “Eveline” is then considered to have feminist values. Feminism is an awareness of gender injustice that befalls women, both in the family and society. The research uses a descriptive form of research. The data source in this research is the short story “Eveline” by James Joyce. Published in 1904 in Dublin, Ireland. The data used in this study are all short story quotations in the form of words, phrases, sentences and paragraphs in the short story “Eveline” by James Joyce that illustrate feminism. Eveline is portrayed as a girl who generally does housework (stereotypical of women’s duties as house caretakers). Eveline’s consideration of her choice to stay with the grueling routine with her family and abusive father, or to run away with her boyfriend. This short story also illustrates how her father's abusive treatment was initially only shown to the boy. The story then closes with Eveline's choice to stay and not go with her boyfriend. This choice is made with uncertainty and doubt. However, Eveline realizes that her presence in the family is not just that of a girl who does ordinary housework, but is a carrier who maintains the integrity of her family. A literary work exists alongside the social values that exist in society. The short story “Eveline” written by James Joyce in 1904 is a work that raises the female point of view in the story. Eveline’s point of view as a woman used in the short story succeeds in emphasizing many feminist values, as well as emphasizing the role of women who have often been marginalized by society.